A quality and reliability improvement strategy for a small- and medium-sized manufacturing enterprise: a case study. (30th July 2008) - Aw, K.C.; Xie, S.Q.; Haemmerle, E.
The aim of this paper is to demonstrate how a Small- and Medium-sized Manufacturing Enterprise (SME) in New Zealand strives to improve its product Quality and Reliability (Q&R) through a proposed Q&R improvement programme. This was based on the work conducted for an electronic company in Auckland, New Zealand. The approach taken was to design a Q&R improvement programme based on reviews of its historical data, available facilities, future goals and benchmarking. To maintain confidentiality, the name of the company is omitted in this paper. Most SMEs are low volume manufacturers and it is unrealistic to generate Q&R data from large sample sizes. Despite this, Q&R has become an important factor for them to compete in the global market. A strategy has to be developed to produce products of high Q&R level. This strategy has been proven effective and has been integrated into the company's continuous Quality Improvement Program (QIP).